Accelerating Children's Literacy Competence at Kalen Village through Assistance of Literacy-Based Activities - Syifa Khuriyatuz Zahro; M Hafidh Nashrullah; Agung Novianto; Anindya Pradipta Hutami; Ilmiatul Khoiriyah (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2022)
Indonesian children’s literacy competencies are still a problem. To accelerate the development of the competence, the community service team of Unisda implemented assistance to exemplify copious literacy-based activities both in school and in the community at Kalen village where the problem of the inappropriateness of literacy-based practices, and the unavailability of a literacy support environment were found. The program was targeted to children of elementary school age of Kalen Village, Lamongan, East Java, Indonesia. Several planned programs were accomplished through three phases; preparation that included identifying community problems and deciding on offered solutions, implementation that covers the execution of the planned programs in twelve weeks, and evaluation. To evaluate the activities, an analysis of observation, interview, and a survey was conducted qualitatively. The result indicated that three major programs were evidenced to accelerate children's literacy competence. The success of the program, therefore, was urgently suggested to be a continuous program to be arranged by the village government.